The Model Development Training to Increase Competence of Teacher on Education of Citizenship Based on Multiculture - Ahmad Jamalong (STKIP Singkawang, 2020)
This research purpose to increase the competence of Teachers in Education of Citizenship in Junior High School at Pontianak City. The research to use development method Research & Development (R & D). The research subject of 24 teachers of Citizenship Education in Junior High School at Pontianak City which active in container Conference Teacher Subject Matter (CTSM). The approach to use in this research of Research & Development (R & D). Technique collection data was with observation form, questionnaire Likert scale, open questionnaire, interview compass, document analysis, Group Focus Discussion, documentary study, and test. This research purpose to describe: (1) Training model now to use by the teacher, (2) To design development model and device of the implementation training of Citizenship Education basis on multicultural through empowerment Conference Teacher Subject Matter, and (3) Final model of the implementation training of Citizenship Education through Empowerment Conference Teacher Subject Matter to increase competence pedagogical and professional of Teacher in Junior High School at Pontianak City. This results of the research concluded that: (1) Final model of training Citizenship Education bases on multicultural through the empowerment of Conference Teacher Subject Matter (CTSM) can be increase competence pedagogical and professional of teacher subject matter Citizenship Education, was increase competence Pedagogical was increasing ability development syllabus, the increased ability in The Planning of Implementation Learning (PIL), the formulation Basic Competence (BC), the increased ability of the implementation of Learning, and ability learning evaluation, (2) Final model of training Citizenship Education basis on multicultural through the empowerment of CTSM more effective to increase ability Pedagogical and competence professional of teacher Citizenship Education in Junior High School at Pontianak City.